Aplikasi silika dan penerapan cekaman kekeringan terkendali dalam upaya peningkatan produksi dan mutu simplisia binahong (Anredera cordifolia) - Jeni Laras Utami; Budi Adi Kristanto; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2020)
ABSTRACT The purpose of this research was to examine the application of silica in the cultivation of controlled drought stress to obtion simplicia with high flavonoid content. The research was arranged in a completely randomized design with 4x2 factorial with 4 replications. The first factor was drought stress duration consisted of watering every 2 days (controls), 6, 10, and 14 days before harvest. The second factor was the application of silica consisted of without silica (control) and the application of silica with a dose of 150 kg SiO2/Ha. The data were analyzed by variance analysis and continued by Duncan’s Multiple Range Test. The result of the study showed that the aplication of silica increased plant height, number of leaves, fresh weight and dry weight production of simplicia, and flavonoid content. Application of drought stress with a duration of up to 8 days before the simplicia harvested was not reduced plant height, number of leaves, production of fresh weight and dry weight of simplicia, but increased flavonoid content. Application of silica increased the number of leaves and the dry weight of simplicia in the application of drought stress to a duration of zero, 4, and 8 days. The application of drought stress with a duration of 8 days before harvested and silica application increased flavonoid content without reducting the production of dry weight of simplicia.Keywords : binahong, drought stress, flavonoids, silica ABSTRAK Penelitian ini bertujuan untuk mengkaji aplikasi silika pada budidaya tanaman binahong dengan penerapan cekaman kekeringan terkendali untuk memperoleh simplisia dengan kandungan flavonoid tinggi. Penelitian menggunakan rancangan percobaan acak lengkap faktorial 4x2 dengan 4 ulangan. Faktor pertama durasi cekaman kekeringan terdiri dari penyiraman 2 hari sekali (kontrol), 6, 10, dan 14 hari sebelum simplisia dipanen. Faktor kedua aplikasi silika terdiri dari tanpa aplikasi silika (kontrol) dan aplikasi silika dosis 1500 kg SiO2/Ha. Analisis ragam dilakukan dengan uji F dan uji lanjut Duncan Multiple Range Test (DMRT) pada taraf 5%. Hasil penelitian dapat menunjukkan bahwa aplikasi silika meningkatkan tinggi tanaman, jumlah daun, produksi berat segar dan berat kering simplisiaserta kandungan flavonoid simplisia binahong.Penerapan cekaman kekeringan dengan durasi sampai 8 hari sebelum simplisia dipanen tidak menurunkan tinggi tanaman, jumlah daun, produksi berat segar dan berat kering simplisia, tetapi meningkatkan kandungan flavonoid simplisia. Aplikasi silika meningkatkan jumlah daun dan berat kering simplisia pada penerapan cekaman kekeringan sampai durasi nol, 4 dan 8 hari. Penerapan cekaman kekeringan dengan durasi 8 hari sebelum simplisia dipanen dan aplikasi silika meningkatkan kandungan flavonoid simplisia binahong tanpa menurunkan produksi berat kering simplisia.Kata kunci : binahong, cekaman kekeringan, flavonoid, silika